Prospects of cloud technologies use in the training process of comprehensive educational institutions of Ukraine - Вакалюк, Тетяна Анатоліївна; Поліщук, Вікторія Василівна (Pedagogy of Higher and Secondary Education, 2015)
Vakalyuk T. A., Polishchuk V. V. Prospects of cloud technologies use in the training process of comprehensive educational institutions of Ukraine. On the basis of analysis of scientific literature the prospects of cloud technologies use in comprehensive educational institutions of Ukraine are concidered. The prospects of cloud services such as Office 365, Google Apps, Prezi are analyzed. Examples of their use in training process of comprehensive educational institutions are given. It is analysed that cloud technologies solve the problem of educational institutions to update software and hardware timely.